Creek Paths and Federal Roads : Indians, Settlers, and Slaves and the Making of the American South - Hudson, Angela Pulley (Book collections on Project MUSE., 2010)
In Creek Paths and Federal Roads, Angela Pulley Hudson offers a new understanding of the development of the American South by examining travel within and between southeastern Indian nations and the southern states, from the founding of the United States until the forced removal of southeastern Indians in the 1830s.During the early national period, Hudson explains, settlers and slaves made their way along Indian trading paths and federal post roads, deep into the heart of the Creek Indians' world. Hudson focuses particularly on the creation and mapping of boundaries between Creek.